Rancang Bangun Emergency Button Berbasis LORA - Febriyan, Muhammad Fadhiil; Ziad, Ibnu; Suroso, Suroso (PROtek : Jurnal Ilmiah Teknik Elektro, 2020)
There is no denying that wireless communication technology is a very important component of modern society. One aspect of modern society where the application of wireless communication technology has tremendous potential is in an emergency. This is especially true in weak places and cannot be reached at all by cellular signals. A good example would be the application of wireless communication technology to transmit data about the emergency button is mountained. Nowadays in the mountain all those things can happen when the moment, the champion can experience, hurt, or sick in the middle. Therefore, our goal in this study is to develop and test an affordable wireless communication system for the swimming state center when performing applications. The system uses microcontrollers and communication systems that use Arduino and LoRa as Transceivers and Receivers. The system was successfully tested in the field and obtained data with a distance of 1.2 Km.